Undergraduate nursing students’ experiences during international clinical placement: A scoping review - Lasse Andreassen; Simen A. Steindal; Jyoti Sarin; Benedicte Sørensen Strøm (International Journal of Nursing Studies Advances)
Background: Immigration, combined with the growth of multicultural societies, has increased patient diversity, highlighting the need for cultural competence in healthcare to prepare nurses to understand the nature of global health. Nurses should have knowledge to understand and respect how culture influences patients’ health needs, access to healthcare services, and the health-related decision-making process. Offering international clinical placement to nursing students is one way to increase this cultural competence. No scoping review has mapped undergraduate nursing students’ experiences during international clinical placement. Objectives: To provide an overview of published studies on undergraduate nursing students’ experiences during international clinical placement. Design: A scoping review. Methods: A systematic search was performed in three databases (CINAHL, Medline, PubMed). The inclusion criteria were: 1) studies with quantitative, qualitative or mixed methods design, 2) studies reporting undergraduate nursing students’ experiences of international clinical placement and 3) studies published in peer-reviewed journals in the English language between January 2008 and February 2023. Pairs of authors independently assessed eligibility and extracted data. Data were thematically grouped. Results: 42 papers were included, 39 studies employed a qualitive design, while 3 studies employed a quantitative design. All studies included students from Western countries with international clinical placement in non-Western countries. Most students had international clinical placement in hospitals, with a wide range of length of exchange. Four thematic groupings were identified: 1) developing cultural competence through culture shock, 2) a novel way of practicing nursing due to a different nursing role, 3) the essential role of the supervisor in learning outcomes and 4) the impact of language barriers on learning outcomes. Conclusions: Students developed cultural competence by experiencing culture shock when exposed to an unfamiliar cultural environment. While they often reacted negatively to these differences, they often adjusted their prejudices and biases over time. Language skills were the greatest barrier to achieving learning outcomes, creating more frustration than cultural barriers. There is a need to investigate how non-Western students experience studying in a Western country.